Recitation of the Succession of the Sunan Kudus in Cultural Da'wa - Bekti Taufiq Ari Nugroho; Choeroni Choeroni; M. Minanur Rohman (Indonesian Academy of Social and Religious Research (IASRR), 2020)
Wali comes from Wala or Waliya which means close, has a role in continuing the prophetic mission. In the Quran, this term is used to mean a relative, friend or protector. In carrying out the role of continuing the mission of prophecy, the saints who are more familiarly called Walisongo always invite Islam and Ahl al-Sunnah Wa al-Jama'ah, the da'wa used by Walisongo in realizing its mission is the application of the methods developed by Sunni Sufis in imparting teachings. However, the methods of preaching that are carried out by the saints are different, the values ​​of pluralism as practiced by Sunan Kudus are very different from other saints, where Sunan Kudus used methods by utilizing traditional symbols and beliefs of the local community, evidence of Da'wa methods are still visible today, namely the shape and style of the building of the al-Aqsa mosque, minarets, gates, and showers (ablution places) which are actually symbols of the eight Buddhist paths, each of which is given a statue of the head of Kebo Gumarang as a permanent Buddhist teaching. preserved as part of cultural assimilation.